Desempenho e qualidade da carne de suínos suplementados com magnésio e creatina no período pré-abate - Olivia Didier Machado (2007)
To evaluate the effect of dietary magnesium and creatine supplementation, during five days before slaughter, on performance and pork quality were used 24 crossbred pigs, and live weight of about 102,2 kg. The animals were allotted in a completely randomize block desing with four dietary treatments and six replicates per treatment and one pig per pen. The commercial dietary were supplemented with: T1 = Control (without supplementation); T2 = 36g of magnesium sulphate 9% (3,2g of magnesium); T3 = 26g of creatine monohydrate 98% (25g of creatine); T4 = 36g of magnesium sulphate 9% (3,2g of magnesium) with 26g of creatine monohydrate 98% (25g of creatine). The animals were slaughtered in the end of experimental period in a commercial abattoir. The average gain, feed conversion and carcass yield were not affected by treatments. All animals supplemented had higher (P<0,05) initial pH value compared to pigs fed the control diet. There were a significant increase ultimate pH to T2 and T3 animals compared to T1. The T2 pigs had meat less pale, while the T3 and T4 pigs had meat more red compared to the others treatments. There was no effect of treatments on water holding capacity and shear force. The results indicate the treatments T2 and T4 had the best results by increase ultimate pH and meat fresh color improve.